(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article analyzes the relationship between judicial bias, administrative morality and the republican principle in the context of the annulment of Lava Jato decisions. Judicial bias directly harms impersonality and equality, pillars of the republican principle, compromising trust in institutions and subverting due legal process. The nullity of evidence obtained through illicit means reaffirms the importance of guaranteeing an ethical process and in accordance with constitutional dictates. Furthermore, administrative morality requires that public power be exercised in an ethical and transparent manner, providing protection against abuse and undue favoritism. The article concludes that judicial impartiality and administrative morality are fundamental to the preservation of the Democratic Rule of Law, ensuring that judicial decisions are fair and legitimate, always guided by the public interest and the common good.